Student bloggers' perceptions of blogging to enhance writing skills / Noor Shafiqah Shamshudin - Shamshudin, Noor Shafiqah (Faculty of Education, 2014)
Blogging enables people to express themselves freely and share their ideas online. This innovation also helps students to find an alternative way to practice writing in English language outside the classroom. This study aims to examine the students' perspective on using to enhance their writing skills. This study also determines the usefulness of using blogs to provide the opportunity for students to use the language after school. An online survey was conducted by using Sogosurvey.com which was responded by 50 secondary school students who are bloggers. The study shows positive responds of blogging in enhancing writing skills. Blogging helps students to gain self confidence in writing and improve their writing skills.